2022
DOI: 10.1042/bsr20210941
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of changes in the activity and function of dry eye-associated brain regions using the amplitude of low-frequency fluctuations method

Abstract: Objective: The local characteristics of spontaneous brain activity in patients with dry eye (DE) and its relationship with clinical characteristics were evaluated using the amplitude of low-frequency fluctuations (ALFF) method. Methods: A total of 27 patients with DE (10 males and 17 females) and 28 healthy controls (HCs) (10 males and 18 females) were recruited, matched according to sex, age, weight, and height, classified into the DE and HC groups, and examined using functional magnetic resonance imaging sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Thus, for dry eye to be defined with the greatest degree of precision and to be distinguished from other ocular surface disorders, the etiological factors are essential. In addition, the symptoms dry eye syndrome are associated with malfunction in particular brain regions [ 31 ]. In addition, gut microbiome disturbance or dysbiosis was identified to be associated with the development of dry eye, particularly primary Sjogren’s disease ( Figure 1 ) [ 32 ].…”
Section: Chronic Eye Diseases That Require Long-acting Therapymentioning
confidence: 99%
“…Thus, for dry eye to be defined with the greatest degree of precision and to be distinguished from other ocular surface disorders, the etiological factors are essential. In addition, the symptoms dry eye syndrome are associated with malfunction in particular brain regions [ 31 ]. In addition, gut microbiome disturbance or dysbiosis was identified to be associated with the development of dry eye, particularly primary Sjogren’s disease ( Figure 1 ) [ 32 ].…”
Section: Chronic Eye Diseases That Require Long-acting Therapymentioning
confidence: 99%
“…The ALFF measures the low-frequency oscillation intensity of BOLD time courses in rs-fMRI (Zang et al, 2007;Guo et al, 2022). Although the exact biologic mechanisms of ALFF remain unclear, plenty of research has indicated that the ALFF changes are associated with local neuronal activity (Cui et al, 2017;Wang et al, 2019;Sun et al, 2022). ReHo measures the similarity in the time series of a given voxel to its nearest neighbors, which indicates that the ReHo alterations are associated with the coherence of spontaneous neuronal activity (Zang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, higher brain functions may be involved in the onset and progression of DE symptoms [19][20][21]. We previously used menthol to investigate cold sensitivity and its association with short TBUT DE and found no difference in cold sensitivity between individuals with short TBUT DE and normal eyes.…”
Section: Introductionmentioning
confidence: 99%